SORPTION OF HEAVY METAL CATIONS BY LOW-TEMPERATURE DEPOSITS OF PACIFIC HYDROTHERMAL FIELDS - Novikov G.V.; Bogdanova O.Yu.; Vikent'ev I.V. (My University, 2006)
Cation exchange reactions with participation of heavy metals Mn, Co, Ni, Cu, Zn, Cd, Ba, and Pb were studed in oceanic low-temperature hydrothermal deposits of various mineral compositions and in hydrogenic Fe-Mn crusts. Individual minerals and their assemblages differ significantly in absorptive capacity, which increases in the following order: hematite ≪ Si-protoferrihydrite < protoferrihydrite < geothite < nontronite ≪ Fe-vernadite + Mn-feroxyhyte < Fe-free vernadite < bernessite + Fe-free vernadite < bernessite; i.e., it successively increases from the mineral with a coordination type of lattice to minerals with a layer-type structure. The exchange complex of all minerals includes Na+, K+, Ca2+, and Mg2+, i.e., the main cations of seawater. In Mn minerals, Mn2+ is the main exchange component. The contribution of all the mentioned cations to the exchange capacity of minerals is as high as 90-98%. The highest absorptive capacity among the examined low-temperature oceanic deposits is characteristic of hydrothermal Mn minerals. Their capacity exceeds substantially that of hydrothermal oxides, hydroxides, Fe-aluminosilicates, and hydrogenic Fe-Mn minerals. The absorptive capacity of all examined Mn minerals relative to heavy metals increases in the same order: Ni < Zn < Cd < Mn < Co < Pb < Cu. © Pleiades Publishing, Inc. 2006.